Monocyte function and trafficking in cardiovascular disease - Pardali, Evangelia; Waltenberger, Johannes (Thrombosis and Haemostasis, 2012)
Monocytes are key effectors of the immune homeostasis and play a crucial role in (vascular) injury repair. Despite their role in immune defense and tissue repair mechanisms, monocytes are also involved in several pathological conditions such as autoimmune and cardiovascular diseases as well as cancer. This suggests that monocytes can be used as diagnostic and as therapeutic targets. A better understanding and characterisation of monocytes and their function in both physiological and pathological situations is thus of great interest. This review focuses on recent advances on the role of monocytes in cardiovascular diseases and describes the value of monocytes as either disease marker or therapeutic target for (cardio)vascular diseases.
Keywords: Monocytes; cardiovascular disease; atherosclerosis; myocardial infarction